PERSONAL DATA PROTECTION ACT 2010 (ACT 709) = AKTA PERLINDUNGAN DATA PERIBADI 2010 (AKTA 709) - Malaysian Employers Federation 11797 (Petaling Jaya : Malaysian Employers Federation, 2014)
Johor Corporation (JCorp);